KUKERTA TERPADU PADA MASA PANDEMI DI DESA RANCASUMUR KECAMATAN KOPO KAB. SERANG - Toton Riyadi (JIPAM : Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Real Work Lectures and Field Experience Practices (KUKERTA-PPL) have been held in Rancasumur Village, namely the Abdul Aziz Sebe Islamic Education Foundation for 6 weeks from January 6, 2021 to February 16, 2021. The school that is the destination of KUKERTA-PPL is located at Jalan Cikande – Kopo km 5 Sebe Rancasumur Village, Kopo District, Kab. Attack, because during the pandemic, the time is shortened. Various Integrated KUKERTA programs have been implemented. The KKN/PPL activities that have been carried out began with school observations, program planning, program consultations with foundations and KUKERTA supervisors in implementing the planned program. The Integrated KUKERTA activities carried out include the planning, preparation, teaching practice, and implementation of community and school activities. The results achieved from the implementation of the Integrated KUKERTA are providing changes in people's mindsets, unhealthy habits and participating in social and religious activities, active and interesting learning processes, and training students' process skills in learning, especially religious lessons, Indonesian language, and general lesson. Broadly speaking, the programs that have been prepared can run well and can provide benefits for the personal progress of the compilers, students, teachers and schools as well as the Rancasumur village community for the better now and in the future. The Integrated KUKERTA program, apart from being a vehicle for training and learning for students, is also a way for the Assalamiyah Islamic High School to contribute in transforming religious, social values ​​to the community and education to the school. The hope is that it is not only a transfer of knowledge given by students, but also a transfer of value. The existence of KUKERTA Terpadu students is expected to be able to make changes as an effort to change the mindset of the community and villages and advance Indonesian education